Perception of agro-industrial engineering students on global innovation indices - Tarazona, Vitelio Asencios; Vergara- Medrano, Segundo Edilberto; Valencia – Salazar, Edilberto; Ruiz –Yance, Iris Olivia; Diaz-Gonzales, Eudualdo (International Journal of Innovative Research and Scientific Studies, 2025)
The objective was to evaluate the level of conceptual perception of higher education students regarding the Global Innovation Indices. The sample consisted of 77 agro-industrial engineering students from UNIA, divided into three groups: Group I, students of Cycle III; Group II, Cycle VI; and Group III, Cycles VII and X, which were selected through intentional non-probabilistic sampling. The Kruskal-Wallis non-parametric test was conducted, which showed the non-significance of the differences between groups and within each group. 57.4% of students presented a perception of the values that they do not understand and do not give importance to the Global Innovation Indices, compared to 42.7% who indicated that they do understand and give importance to it. No significant statistical difference was demonstrated between the groups and within each reference group at the levels of perception of the Global Innovation Indices.